Long receptor residence time of C26 contributes to super agonist activity at the human β2 adrenoceptor - Rosethorne, Elizabeth M.; Bradley, Michelle E.; Gherbi, Karolina; Sykes, David A.; Sattikar, Afrah; Wright, John D.; Renard, Emilie; Trifilieff, A.; Fairhurst, Robin A.; Charlton, Steven J. (American Society for Pharmacology and Experimental Therapeutics (ASPET), 2016)
Super agonists produce greater functional responses than endogenous agonists in the same assay, and their unique pharmacology is the subject of increasing interest and debate. We propose that receptor residence time and the duration of receptor signaling contribute to the pharmacology of super agonism. We have further characterized the novel β2 adrenoceptor agonist C26 (7-[(R)-2-((1R,2R)-2-benzyloxycyclopentylamino)-1-hydroxyethyl]-4-hydroxybenzothiazolone), which displays higher intrinsic activity than the endogenous ligand adrenaline in cAMP accumulation, β-arrestin-2 recruitment, and receptor internalization assays. C26 recruited β-arrestin-2, and internalized the Green Fluorescent Protein (GFP)-taggedβ2 adrenoceptor at a slow rate, with half-life (t1/2) values of 0.78 ± 0.1 and 0.78 ± 0.04 hours, respectively. This was compared with 0.31 ± 0.04 and 0.34 ± 0.01 hours for adrenaline-mediated β-arrestin-2 recruitment and GFP-β2 internalization, respectively. The slower rate for C26 resulted in levels of β-arrestin-2 recruitment increasing up to 4-hour agonist incubation, at which point the intrinsic activity was determined to be 124.3 ± 0.77% of the adrenaline response. In addition to slow functional kinetics, C26 displayed high affinity with extremely slow receptor dissociation kinetics, giving a receptor residence half-life of 32.7 minutes at 37°C, which represents the slowest dissociation rate we have observed for any β2 adrenoceptor agonist tested to date. In conclusion, we propose that the gradual accumulation of long-lived active receptor complexes contributes to the increased intrinsic activity of C26 over time. This highlights the need to consider the temporal aspects of agonist binding and signaling when characterizing ligands as super agonists.